Peran Brand Love sebagai Mediasi Hedonic Product dan Self-Expressive Brand Terhadap Brand Loyalty - Amelindha Vania; Kartika Anggraeni Sudiono Putri (University of Merdeka Malang, 2020)
This study aims to analyze the impact of hedonic products and self-expressive brands towards brand love and brand loyalty to Starbucks Coffee customers in Malang City. This study also analyzes the role of brand love as a mediator become an intermediary for hedonic products and self-expressive brands in influencing brand loyalty. The research object uses the Starbucks Coffee brand because Starbucks coffee is categorized as a hedonistic item and Starbucks builds a special bond with its customers. This type of research is descriptive quantitative. The research sample consisted of 125 customers of Starbucks Coffee Mall Dinoyo Malang with the sampling technique was carried out accidental sampling. Structural Equation Modelling (SEM) method using the IBM SPSS and IBM AMOS version 24.0 program is a method for analizyng data in this study. The results show that both hedonic products and self-expressive brands have a positive and significant impact on brand love. However, hedonic products and self-expressive brands do not have a direct influence on brand loyalty. Hedonic products and self-expressive brands have a significant effect on brand loyalty with the help of brand love as a mediator. Research also proves brand love has a positive and significant impact on brand loyalty.